(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of our study was to identify the possible risk factors for renal dysfunction after total hip joint replacement surgery. Study Design: Observational cohort study Place and Duration of Study: This study was conducted in Orthopedic Department of Lady Reading Hospital, Peshawar from March 2013 to February 2014. Materials and Methods: A study was conducted among 212 consecutive primary hip joint replacements performed. According to the RIFLE criteria, increased postoperative serum creatinine was considered indicative of postoperative renal injury. Results: Eighty-one patients (14.1 %) had significant moderate or severe postoperative renal dysfunction in which 4 patients (1.9 %) acquired severe and permanent renal impairment. Conclusion: We identified advanced age, hypertension, general anesthesia, high ASA scores, low intra-operative systolic BP, and prophylactic dicloxacillin as significant risk factors. Smoking, diabetes mellitus, high BMI, gender, and duration of surgery were not identified as significant risk factors.